(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
This article argues for a ’social vaccine’ in pandemic times that underpins the four basic requirements for global health and equity to flourish by providing a life with security, opportunities that are fair, a planet that is habitable and supports biodiversity and governance to ensure resources are fairly distributed (Baum and Friel, 2020). By a ‘social vaccine’ I do not mean a biological vaccine that is produced in laboratories and injected in arms to produce immunity to the COVID19 virus. A ‘social vaccine’ is an antidote to counteract the consequences and long-term effects of epidemic upheaval, designed from below in participatory and dialogical relationships with those worst affected by its consequences. This article argues that community adult education, which has incessantly prioritised employability skills training, should play a pivotal role in providing a ‘social vaccine’ in pandemic and post-pandemic times. The significance of community adult education is that it seeks to build the curriculum from the inequalities and injustices that people experience in their everyday lives by providing opportunities for individual and collective change.